Do Economics Departments with lower Tenure Probabilities pay Higher Faculty Salaries? - Ehrenberg, Ronald G.; Pieper, Paul J.; Willis, Rachel A. (The Review of Economics and Statistics, 1998)
This Article is brought to you for free and open access by the ILR Collection at DigitalCommons@ILR. It has been accepted for inclusion in Articles